The Importance of Doppler Analysis of Uterine Circulation in Pregnancy for a Better Understanding of Preeclampsia - Medjedovic, Edin; Kurjak, Asim (Medical archives (Sarajevo, Bosnia and Herzegovina), 2021)
The etiology of preeclampsia has still not been completely explained. Early identification of women with the risk of developing preeclampsia is a key goal of antenatal care. To investigate risk factors for preeclampsia from the history, laboratory and ultrasound findings (Doppler). Pregnant women with normal Doppler sonography in the second trimester of pregnancy were classified as a control group, while pregnant women with impaired Doppler in the second trimester were considered as the investigated group with presumably increased risk for preeclampsia. A total number of 80 patients was included in the study (40 patients in each group). The difference of urea, uric acid and lactate dehydrogenase (LDH) in the serum of the control and investigated group was statistically significant, while the differences were not statistically significant for creatinine, aspartate aminotransferase (AST) and alanine aminotransferase (ALT). The presence of a notch sign during assessment of blood flow in uterine arteries in subjects in the investigated group with the diagnosis of preeclampsia had the specificity of 47.62%, and sensitivity of 88.89%. The positive predictive value of a notch sign during assessment of blood flow in uterine arteries as a marker for diagnosis of preeclampsia in the second trimester of pregnancy was 90.91%, and its negative. Systolic and diastolic blood pressure are dependent variables which are predicting preeclampsia, whilst a notch sign in uterine arteries was designated as an independent variable predicting preeclampsia. From the laboratory tests the following parameters were considered as the risk factors for preeclampsia: increasing levels of urea, uric acid, and LDH. Notch sign was considered to be a very strong predictor of preeclampsia, especially if present bilaterally. Doppler sonography in the second trimester of pregnancy is a good predictor for early diagnosis of preeclampsia.